2011
DOI: 10.1111/j.1365-2303.2010.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of micronucleus scoring in fine needle aspirates of ductal carcinoma of the breast

Abstract: MN scoring on routinely stained smears of IDCs was significantly higher than in fibroadenoma and was relatively easy, reliable and reproducible. As MN scoring of grade 1 IDC was similar to fibroadenoma, a larger study should be conducted to compare grade 1 IDC with other benign breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
5
28
1
Order By: Relevance
“…[8,9,16] In our study we noticed a significant difference in occurrence of micronuclei between benign and malignant cases as well as between various grades of malignancy. Similar findings has been described by Samantha S and Goel et al [7,17] Mean micro nuclei value in our study was more than Samantha et al [7] Even our baseline study population showed more micronuclei values as compared to their population of study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[8,9,16] In our study we noticed a significant difference in occurrence of micronuclei between benign and malignant cases as well as between various grades of malignancy. Similar findings has been described by Samantha S and Goel et al [7,17] Mean micro nuclei value in our study was more than Samantha et al [7] Even our baseline study population showed more micronuclei values as compared to their population of study.…”
Section: Discussionsupporting
confidence: 92%
“…[1] Micronuclei scoring in routinely stained smears has been applied to study the different epithelial preneoplastic and neoplastic conditions of the head and neck, cervical intraepithelial lesions, cervical carcinomas and also in liver carcinogenesis. [6,7,8,9] Aim of our study was; 1. To score the spontaneously o c c u r r i n g m i c ro n u c l e i i n t h e b a s e l i n e population (fibroadenomas) and infiltrating ductal carcinoma, 2.…”
Section: Introductionmentioning
confidence: 99%
“…Besides fine needle aspiration smears, the frequency of MN helped to detect atypical cells in urine samples and ascitic effusion, indicating malignancy (24,30,31). Moreover, our findings are consistent with the findings of studies on the frequency of MN in exfoliative, fine needle aspiration, and effusion smears (22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Suspicious Cytology (N = 22)supporting
confidence: 90%
“…Consistently with the literature, we found that all the cytological smears with a malignant outcome had a significantly higher MN count compared to benign ones (P < 0.001, Table 1). According to the literature, in the fine needle aspirates of breast lesions, ductal carcinoma cells had significantly higher MN counts than cells of fibroadenoma (25,26). Likewise, in cervical smears, cases of high-grade intraepithelial lesions or invasive carcinoma had more micronucleated cells than cases of reactive changes (27).…”
Section: Suspicious Cytology (N = 22)mentioning
confidence: 95%
“…A micronucleus is the small nucleus that forms whenever a chromosome or its fragment is not incorporated into one of the daughter nuclei during cell division and it serves as an indicator of CIN. Samanta et al reported that in the evaluation of the number of micronuclei in 1000 cells from ine needle aspiration samples of the breast, cancer cells showed a higher number of micronuclei than benign lesions [44]. Tyagi et al assessed the number of anaphase bridges, multipolar mitoses, micronuclei, and nuclear budding in 1000 cells in Giemsa stained smears of ascitic luid and found that these markers were correlated with the cytological diagnosis [30].…”
Section: Morphological Markers Of Chromosomal Instabilitymentioning
confidence: 99%